On teaching different amplifiers using a "T" Transistor Model - Escoto, Miguel T., Jr.
This paper presents a practical circuit approach in the analysis of an emitter-coupled differential amplifier pair. Development and analysis center around parameter keywords like differential gain (AD), common mode gain (AC) and common mode rejection ratio (CMRR). The Ebers-Moll Model is used to derive a "T" transistor model for signal analysis.